2023
DOI: 10.1177/20530196231153925
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and absence: Human-microbial co-evolution in the Anthropocene

Abstract: Human-microbe relations have undergone a profound shift over the past 100 years. The discovery of antibiotics, increasing levels of pollution, and urban and agricultural intensification have led to the proliferation and diversification of novel resistance genes and microorganisms. This abundance has unfolded against a backdrop of microbial absence that is the other side of the antimicrobial coin; reductions in the quantity and diversity of human-microbe interactions are now registering as epidemics of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 149 publications
0
0
0
Order By: Relevance
“…Animals' geographies commitment to the indeterminate nature of large organisms, I suggest, is consistent with recent scientific reconceptualisations which frame microbial communities as intelligent and hyper-adaptive life forms (e.g., Westerhoff et al, 2014), a theme also taken up in recent social scientific and geographic research (Clark and Hird, 2013;2018). Other research has discussed this adaptability particularly in its relation to anthropogenic environments of urbanisation, pollution, and antimicrobial warfare (Bradshaw, 2023), which the current paper extends through examples of microbial agency in water treatment, sewage treatment, and spontaneous urban ecological succession.…”
Section: Animals' Geographies and Urban Ecologiessupporting
confidence: 74%
See 2 more Smart Citations
“…Animals' geographies commitment to the indeterminate nature of large organisms, I suggest, is consistent with recent scientific reconceptualisations which frame microbial communities as intelligent and hyper-adaptive life forms (e.g., Westerhoff et al, 2014), a theme also taken up in recent social scientific and geographic research (Clark and Hird, 2013;2018). Other research has discussed this adaptability particularly in its relation to anthropogenic environments of urbanisation, pollution, and antimicrobial warfare (Bradshaw, 2023), which the current paper extends through examples of microbial agency in water treatment, sewage treatment, and spontaneous urban ecological succession.…”
Section: Animals' Geographies and Urban Ecologiessupporting
confidence: 74%
“…Further to this, microbiologist Michael Gillings (2017 has suggested that, at the molecular level, human actions over the past century have increased the rate of microbial evolvability per se, by selecting for increased rates of lateral genetic transfer and hyper-mutable strains through unprecedented levels of chemical stress. Urban infrastructures synergise with and reinforce these molecular processes at the macroscale (see Bradshaw, 2023). Such arguments further the notion that the model of human-microbial co-evolution glossed above is certainly not about humans controlling and directing microbial agencies down preferred paths.…”
Section: Discussion: Human-microbial Co-evolution In Urban Settingsmentioning
confidence: 89%
See 1 more Smart Citation